Praktik Sende dalam Prespektif Ekonomi Syariah di Desa Rejoagung Kecamatan Ngoro Kabupaten Jombang - Hidayatulloh, Rizky; Anwar, Moch. Khoirul (Jurnal Ekonomika dan Bisnis Islam, 2020)
The practice of sende is one of the financing solutions commonly used by the people of Rejoagung village. The majority of Rejoagung villagers are followers of Islam, so whatever is done in living their lives must be in accordance with the guidance of the Shari’ah no exception in the implementation of the practice of sende. Qualitative descriptive is a method used in this study, which aims to determine the implementation of sende practices in the Rejoagung village and Islamic economic perspective on these practices. Based on the research that has been done shows that the practice of sende is a practice that involves two parties between the debtor and the creditor with the rice fields as collateral for the debt. Rice fields can be used by lenders so that those who are in debt can make up for it. According to the Shari’a, the practice has legitimacy in accordance with the opinions of the ulama.